Les archives de l'Assemblée nationale du Québec - Bernier, Gaston (Archives, 2004)
Keywords: Archives

Les archives en milieu muséal: le cas du Musée McCord - Cartier, François (Archives, 2005)
Keywords: Archives; Musée McCord; Musées

Le projet de sauvegarde de la collection Bens Delicatessen. Bien plus que les archives du smoked meat! - Cartier, François (Archives, 2008)
Keywords: Archives; Confédération des syndicats nationaux; Musée McCord; Musées; Restaurant

L’archive littéraire à la rescousse de l’histoire: le cas des Comédies du Statu quo (1834) - Desjardins, Nancy (Archives et fabrique du textile littéraire, 2001)
Keywords: Archives; Papineau, Louis-Joseph; Rébellions

A Heuristic Archive: Jean-Paul Gill's Red Light Photographs - Guillaume, Philippe (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Archives; Patrimoine; Photographie; Quartiers; Saint-Laurent (quartier)

Révolution dans les archives...et dans la reconstitution du passé - Deslandres, Dominique (Les cahiers des Dix, 2023)
Keywords: Archives

L’ère des archives québécoises sur le Web - Robert, Mario (Cap-aux-Diamants, 2014)
Keywords: Archives; Archives municipales

Répertoire du fonds François Déziel, FN-0664 - Lalancette, Christian; Archives du Séminaire de Trois-Rivières. (Archives du Séminaire de Trois-Rivières, 2000)
Keywords: Peinture

Les procès en sorcellerie, des archives longtemps négligées : le cas de Montréal - Pettigrew, Stéphanie (Revue d'histoire de la Nouvelle-France, 2023)
Keywords: Archives; Tribunaux

''Au-delà du syndrome de la «citation payante»'': les archives vivantes et la recherche réciproque en histoire orale - High, Steven (Revue d'histoire de l'Amérique française, 2015)
Keywords: Archives; Histoire

La revue Archives à travers ses vingt dernières années d’existence, 1988-2008 - Gagnon-Arguin, Louis (Archives, 2009)

Les archives du réseau institutionnel canadien-français conservées au Québec et à Ottawa, 1834-1973 - Dumas, François; Garon, Louis; Léveillé, Marie (Archives, 2004)

L'odyssée des archives de la Société Historique de Montréal - Robert, Mario (Montréal en tête, 2019)
Keywords: Archives; Société historique de Montréal

Female Authorship, Incomplete Archives, and the Periodical Press in Nineteenth Century Montreal: The Case of Rosanna Mullins Leprohon - Cabajsky, Andrea (Port Acadie, 2022)
Keywords: Archives; Femmes; Écrivains

Recovering Identities from the Judicial Archives of Quebec - Olson, Sherry; Poutanen, Mary Anne (Histoire sociale / Social History, 2024)
Keywords: Archives; Enfants; Famille; Femmes

La nuit de feu des livres et des archives du Parlement - Gallichan, Gilles (Bulletin d'histoire politique, 2013)
Keywords: Archives; Incendies; Parlement; Torys; Émeutes

L’archive et l’invention littéraire: le cas des Mystères de Montréal d’Auguste Fortier (1893) - Ducharme, Nathalie (Archives et fabrique du textile littéraire, 2001)

Les archives de la Société historique de Montréal. La contribution de la Société historique de Montréal à la sauvegarde du patrimoine archivistique montréalais - Lebeau, Mireille (Montréal en tête, 2008)
Keywords: Archives; Conservation; Histoire; Patrimoine; Société historique de Montréal

L’apport de François Beaudin: la mise en place du rapport Deschênes - Baillargeon, Diane (Archives, 2017)
Keywords: Université de Montréal

Théâtre à Montréal, 1825-1930: un récit visuel mettant en scène des documents patrimoniaux - Léger, Danielle (Archives, 2019)
Keywords: Cartes et plans; Histoire; Patrimoine; Théâtre

Vivre Montréal, 1920-1969 - Fontaine, Julie; Lebeau, Mireille; Robert, Mario (Aux limites de la mémoire, 2011)
Keywords: Archives municipales; Photographie

Guide des archives Barreau du Québec - Barreau du Québec (Service de la gestion de l'information, 2003)
Keywords: Barreau; Droit

Photographes et archives photographiques des quartiers disparus - Robert, Mario (Quartiers disparus: Red Light, Faubourg à M'lasse, Goose Village, 2014)
Keywords: Photographie; Quartiers

Historienne, mentore, libre-penseuse: réflexions autour de l'oeuvre d'Andrée Lévesque - Fahrni, Magda (Profession historienne? Femmes et pratique de l’histoire au Canada français, XIXe-XXe siècles, 2023)
Keywords: Archives; Femmes; Histoire

Quand les archives racontent Montréal - 100 pièces d'exceptions - Bednarz, Nicolas; Forest-Bonin, Anick; Robert, Mario (Publication du Québec et Ville de Montréal, 2013)

Que reste-t-il… des archives de nos premières émissions? - Moreau, Jean-Paul (Cap-aux-Diamants, 2002)
Keywords: Télévision

Photogenic Montreal: Activisms and Archives in a Post-Industrial City - Langford, Martha; Sloan, Johanne (McGill-Queen's / Beaverbrook Canadian Foundation Studies in Art History Series, 2021)
Keywords: Conservation; Patrimoine; Photographie; Quartiers

The Christian Pavilion at Expo 67: Notes from Charles Gagnon's Archive - Kin Gagnon, Monika (Expo 67: Not Just a Souvenir, 2010)
Keywords: Cinéma; Expositions

L'honneur féminin à Montréal à travers les archives judiciaires (1698-1756) - Dufresne, Amélie (Université de Montréal, 2021)
Keywords: Criminalité; Femmes

Boxing Time: Landscape, Feminism and the Archive in Selected Works by Angela Grauerholz - Brock, Lesley L. (Université Concordia, 2004)
Keywords: Paysages; Photographie

Les archives d’enquêtes sur l’éducation au Bas-Canada. Leur contenu et leur utilisation possible - Dufour, Andrée (L'école en chiffres? Réflexions sur les statistiques scolaires au Québec, XIXe-XXe siècles, 2006)

Identities, Communities, and the Infrastructures of History: Creating Canadian Jewish Archives in the 1930s and the 1970s - Menkis, Richard (History, Memory, And Jewish Identity, 2015)
Keywords: Congrès juif canadien; Histoire; Juifs

Le patrimoine documentaire de la paroisse Saint-Enfant-Jésus de la Pointe-aux-Trembles depuis 1669: un trésor d'archives - Belzil, Claude (Atelier d'histoire de Pointe-aux-Trembles, 2013)
Keywords: Pointe-aux-Trembles

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Keywords: Danse; Femmes; Histoire; Musicien; Musique

Westmount public library: Celebrating 125 years (The Westmount Historian, 2024)
Keywords: Archives; Patrimoine; Vitraux; Westmount

Regards sur une Bible hébraïque, une Bible polyglotte et une Bible de Genève conservées par Bibliothèque et Archives nationales du Québec - Crevier Denommé, Isabelle (Ouvrages phares de la Réforme & de la Contre-Réforme dans les collections montréalaises, 2014)
Keywords: Bibliothèque nationale

Voix des esclaves autochtones et des esclavagistes: un cas d’histoire intersectionnelle dans les archives judiciaires de la juridiction de Montréal - Deslandres, Dominique (Les Cahiers des Dix, 2018)
Keywords: Autochtones; Esclaves

Folie, norme et rôles sexuels au Québec dans la seconde moitié du XIXe siècle: quelques observations tirées des archives de la curatelle - Cellard, André (Revue d'histoire de l'Amérique française, 2008)

Femmes devant le tribunal du roi : la culture judiciaire des appelantes dans les archives de la juridiction royale de Montréal (1693-1760) - Deslandres, Dominique (Les Cahiers des Dix, 2017)
Keywords: Criminalité; Esclaves; Femmes; Tribunaux

Images du danger dans les archives judiciaires. Comprendre la violence et le vagabondage dans un centre urbain du début du XIXe siècle, Montréal (1820-1842) - Poutanen, Mary Anne (Revue d'histoire de l'Amérique française, 2002)
Keywords: Délinquance; Itinérance

Reading the Multimedia Archive Surrounding Montreal's Post-War LGBTQ Bars: A Genealogical Return to Madame Arthur and Il était une fois dans l'Est - Pidduck, Julianne (Quebec Studies, 2015)
Keywords: Alcool

À la découverte du Fonds Albéric Bourgeois (1876-1962): thématiques d'une société en transformation, 1899-1957 - Hardy, Dominic; Godin-Laverdière, Julie-Anne; Perron, Nancy (Quand la caricature sort du journal: Baptiste Ladébauche, 1878-1957, 2015)
Keywords: Archives; Bourgeois, Albéric; Caricature; Histoire

Une “vaillante phalange” contre “vieux pontifes”. La réception des Soirées du Château de Ramezay dans le journal Les Débats - Cellard, Karine (Archives et fabrique du textile littéraire, 2001)
Keywords: Ramezay (château de)

Pectus est quod disertos facit: éloquence et sublime dans la Rhétorique (1796) de Jacques-Antoine Houdet - Bélanger, Anne; Landry, Alexandre (Archives et fabrique du textile littéraire, 2001)
Keywords: Collège de Montréal; Communautés religieuses; Sulpiciens

Ironie, sarcasme et dérision dans Le Canadien (1806-1810) - Laquerre, Marie-Lise; Massé, Stéphanie (Archives et fabrique du textile littéraire, 2001)
Keywords: Humour

L'école Saint-Stanislas supérieure et secondaire 1929-1977: l'esprit en mouvement de plusieurs générations - Moineau, Guy; Laprotte, Jean (Archives F.I.C., 2015)

Regards catholiques sur les villes québécoises: une haine à géométrie variable (1918-1939) - Bérubé, Harold (Archives de sciences sociales des religions, 2014)

The Pastness of Allô Police - Straw, Will (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Criminalité; Photographie

Erase and See: The Photogénie of a Metropolis in Progress - Langford, Martha (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Paysages; Photographie

Architecture, Photography, and Power: Picturing Montreal, 1973-74 - Imogen Hammond, Cynthia (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Conservation; McConnell, John Wilson; McConnell, John Wilson (maison); Patrimoine; Photographie; Shaughnessy (maison); Van Horne (maison); Van Horne, William

Through the Lens of Edith Mather: Photographing Demolition and the Transforming City - Southcott, Tanya (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Conservation; Femmes; Patrimoine; Photographie; Rues

Re-activations: Alain Chagnon’s Plateau-Mont-Royal in Translation - Langford, Martha (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Photographie; Plateau Mont-Royal; Quartiers

Le Royal Victoria Hospital et l'instauration du régime d'assurance-maladie québécois 1965-1971 - Charpentier, Alix (Université d'Angers, 2003)
Keywords: Assurance; Hôpitaux; Royal Victoria Hospital

Le Montreal Council of Women / Conseil des Femmes de Montréal, de 1940 à 1967, à travers les questions de planification urbaine, d'immigration et des femmes dans le monde du travail - Hilairet, Sabine (Université d'Angers, 2003)
Keywords: Femmes; Féminisme; Montreal Local Council of Women; Travail

Les guides touristiques d’hôtels montréalais, 1857-1917 – Une stratégie publicitaire - Lefebvre, Michèle (Revue de Bibliothèque et Archives nationale du Québec, 2013)
Keywords: Publicité; Tourisme

Aptitude à signer et usage de la signature chez les ouvriers du bâtiment à Montréal, 1700-1750 - Latouche, Pierre-Édouard (Revue de Bibliothèque et Archives nationale du Québec, 2009)

l'Institut canadien de Montréal: un avant-goût des grands principes de la bibliothèque publique moderne - Lefebvre, Michèle (Revue de Bibliothèque et Archives nationale du Québec, 2010)
Keywords: Institut canadien

Reconstruire Montréal, rebâtir sa fortune - Dufaux, François; Olson, Sherry (Revue de Bibliothèque et Archives nationale du Québec, 2009)
Keywords: Faubourgs; Logement

Du journal à l'oeuvre « Écrire, mon secret, ma captivité, ma vie », Yves Navarre - Lannegrand, Sylvie (Revue de Bibliothèque et Archives nationale du Québec, 2011)
Keywords: Écrivains

Genèse du cycle de « La batèche » de Gaston Miron: de la noirceur aux rives de l'aube nouvelle - Villeneuve, Karine (Revue de Bibliothèque et Archives nationale du Québec, 2011)
Keywords: Miron, Gaston; Poésie

La Revue populaire et Le Samedi – Objets de diffusion de la modernité photographique au Québec, 1935-1945 - Tousigant, Zoë (Revue de Bibliothèque et Archives nationale du Québec, 2013)
Keywords: Photographie

Montréal érotique : pin-up et imagerie de nus chez le photographe de presse Conrad Poirier, 1912-1968 - Godin-Laverdière, Julie-Anne (Revue de Bibliothèque et Archives nationale du Québec, 2013)
Keywords: Photographie; Poirier, Conrad

Les passerelles internationales de la maison d'édition Parti pris - Fabre, Gérard (Revue de Bibliothèque et Archives nationale du Québec, 2010)
Keywords: Godin, Gérald; Idéologies; Parti Pris; Édition

''Il y a des chose qu'une personne cultivée ne peut ignorer''- Le Bulletin de la Société d'étude et de conférences (1915-1967): sa genèse, ses actrices et son contenu. - St-Laurent, Fanie (Revue de Bibliothèque et Archives nationale du Québec, 2012)
Keywords: Femmes

Intimacies in the Neighbourhood: Revisiting Sex Commerce, Families, and Criminal Court Records in Early Nineteenth-Century Montreal - Poutanen, Mary Anne (Family and Justice in the Archives. Historical Perspectives on Intimacy and the Law, 2024)
Keywords: Criminalité; Famille; Femmes; Prostitution

Voices of Litigating Women in New France During the Seventeenth and Eighteenth Centuries. - Deslandres, Dominique (Voices in the Legal Archives in the French Colonial World: "The King is Listening", 2021)
Keywords: Autochtones; Esclaves; Femmes; Noirs

Immigrants italiens dans l'espace social et culturel montréalais. Une synthèse historique - Ramirez, Bruno (Histoires d'immigrations à Montréal, 2014)
Keywords: Italiens

Les juifs sépharades à Montréal - Cohen, Yolande (Histoires d'immigrations à Montréal, 2014)
Keywords: Juifs

Un siècle de vie yiddish à Montréal - Anctil, Pierre (Histoires d'immigrations à Montréal, 2014)
Keywords: Juifs

La communauté écossaise de Montréal. Histoire et questions identitaires - Bourbeau, Catherine (Histoires d'immigrations à Montréal, 2014)
Keywords: Écossais

Many Women, Many Voices. Stories from McGill collections - Cooke, Nathalie; Giuliano, Frédéric; Lyons, Christopher; Owens, Gwendolyn; Sundberg, Jacquelyn; Yearl, Mary (Rare and Special Collections, Osler, Art, and Archives of McGill Library, 2018)
Keywords: Femmes; Université McGill

La Gazette littéraire de Montréal 1778-1779 - Doyon, Nova; Cotnam, Jacques (L'archive littéraire au Québec, 2010)
Keywords: Gazette Littéraire de Montréal; Mesplet, Fleury

La guerre de 1812: Journal de Jacques Viger - Viger, Jacques; Andrès, Bernard (L'archive littéraire au Québec, 2012)
Keywords: Maires; Viger, Jacques

La Grande Guerre de Paul Caron. Chroniques d'un légionnaire canadien-français (1914-1917) - Richard, Béatrice (L'archive littéraire au Québec, 2015)
Keywords: Guerre

Sans différends, point d'harmonie: repenser la criminalité en Nouvelle-France - Paul, Josianne (Septentrion, 2012)
La lecture des archives judiciaires du Régime français remet en question la vision idéalisée d'une Nouvelle-France où la vie des colons se déroulait tel un long fleuve tranquille. Le quotidien des habitants a été ponctué d'escarmouches survenant au cabaret du coin, de paroles injurieuses prononcées à la clôture contre un voisin négligent, de querelles découlant de la vente d'aliments avariés au marché, de chicanes de ménage et, à l'occasion, de pendaisons sur la place publique. En adoptant une méthodologie située à la croisée de l'histoire et de la criminologie, Josianne Paul a voulu comprendre comment, aux XVIIe et XVIIIe siècles, les habitants de Montréal et l'administration coloniale géraient les situations conflictuelles potentiellement criminalisables. En Nouvelle-France, la justice n'était pas un phénomène purement institutionnel et les colons, de même que l'administration royale, avaient à leur disposition plusieurs modes de résolution de conflit qu'ils savaient manipuler avec doigté afin de résoudre de manière durable leurs différends dans le but de maintenir l'harmonie sociale.
Keywords: Criminalité

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord, David Ross; Musée McCord; Musées

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens